Pathological study of a traumatic anthropogenic injury in the skeleton of a spiny butterfly ray (Gymnura altavela) - Montero-Hernández, Gustavo; Caballero, María José; Curros-Moreno, Ángel; Suárez-Santana, Cristian M.; Rivero, Miguel A.; Caballero-Hernández, Lucía; Encinoso, Mario; Fernández, Antonio; Castro-Alonso, Ayoze (Frontiers in Veterinary Science, 2024)
IntroductionExternal injuries in elasmobranchs are frequent findings, either due to inter- or intraspecific interactions or as a result of interaction with human activities. However, the resilience of these species to traumatic injury remains poorly understood. This work provides an insight into the clinical presentation, diagnostic imaging, and pathological features of a severe traumatic injury to the cartilaginous skeleton of a spiny butterfly ray (Gymnura altavela).MethodsAn adult female was found lethargic in the bottom of the coast of Gran Canaria, with an external incised-contused traumatic lesion of 2 cm diameter in the scapulocoracoid cartilage. It was captured and transferred to the Poema del Mar Aquarium for its clinical evaluation and treatment. Despite these efforts, the animal eventually died and was transfer to the Institute of Animal Health and Food Safety (IUSA) for its pathological diagnosis, including a Computed Tomography (CT) study and necropsy.ResultsThe animal presented a marked reduction in hematocrit and hepatosomatic index due a chronic debilitation process. The CT scan revealed a destructive lesion with irregular margins at the level of the right scapulocoracoid cartilage. The main pathological findings were the disorganization of the tesserae layer, appearing as whitish square to rectangular geometric pieces separated from the cartilaginous core. Histologically, these pieces of tesserae were separated from the unmineralized cartilage core and displaced from the adjacent perichondrium, where inflammatory cells infiltrate. Edema and hemorrhages were also observed.ConclusionsThis study reports the first comprehensive description of skeleton trauma in a spiny butterfly ray, including the clinical presentation, diagnostic imaging and the anatomopathological features.